2018
DOI: 10.1177/0044118x18764040
|View full text |Cite
|
Sign up to set email alerts
|

Online, Offline, and Over the Line: Coercive Sexting Among Adolescent Dating Partners

Abstract: This study examines the incidence and correlates of coercive sexting by dating partners among middle and high school students, including sex-based differences and associations with other forms of sexual coercion. Survey data from a study of protective factors for teen dating violence in middle and high school students were examined ( N = 1,236). Of youth who reported at least one dating or sexual partner in the past 12 months, 12% reported coercive sexting victimization and 8% acknowledged pressuring a partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 21 publications
4
81
1
6
Order By: Relevance
“…Moreover, those who experienced these different forms of IPA were significantly more likely than those who did not experience these forms of IPA to report nearly every type of sexting coercion (with the exception that was there was no difference in experiences of defection threat among those who did and did not experience psychological IPA). Our findings support previous research suggesting that coerced sexting is related to partner victimization [ 34 , 35 , 42 , 54 , 55 ] and again reinforce the idea proposed by Ross et al [ 17 ] that sexting coercion be considered part of the construct of IPA. As partner victimization and coercive control extend to digital formats, it will be important to reconceptualize common definitions of IPA and sexual harassment to include digital violence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, those who experienced these different forms of IPA were significantly more likely than those who did not experience these forms of IPA to report nearly every type of sexting coercion (with the exception that was there was no difference in experiences of defection threat among those who did and did not experience psychological IPA). Our findings support previous research suggesting that coerced sexting is related to partner victimization [ 34 , 35 , 42 , 54 , 55 ] and again reinforce the idea proposed by Ross et al [ 17 ] that sexting coercion be considered part of the construct of IPA. As partner victimization and coercive control extend to digital formats, it will be important to reconceptualize common definitions of IPA and sexual harassment to include digital violence.…”
Section: Discussionsupporting
confidence: 92%
“…There are also some data to suggest that sexting may be an additional mechanism through which sexual violence occurs. For example, in their sample of teens, Kernsmith, Victor, and Smith-Darden [ 35 ] examined the relationship between in-person sexual coercion and coercive sexting victimization and perpetration. Their data suggested that, compared to non-victims, victims of coercive sexting were at significantly higher risk of at least one form of in-person sexual coercion from their dating partner [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defined as "the sharing of sexually explicit images, videos, or messages through electronic means", sexting has increased exponentially over the last decade as a modality for teens to explore their sexuality (Madigan et al 2018). Despite documented evidence that adolescent sexting can serve as a mechanism of sexual exploration and empowerment, there also are known correlations between sexting and teen dating violence (TDV) (Kernsmith et al 2018). Here, the most common form of dating violence via sexts is non-consensual nude photographs and coercive language to pressure a partner to have sex (Choi et al 2016).…”
Section: When Sexting Crosses the Line: Educator Responsibilities In mentioning
confidence: 99%
“…Other less reported and understudied motivations related to social purposes, such as having fun, joking, and killing time, to identity construction, such as self-expression and body image acceptance, or to peer group influences, such as imitation or gaining acceptance [8]. Although a number of studies consider sexting as a normative sexual behavior among young people, they also acknowledge that it comes with certain risks [15,16]. A common risk is the intentional, non-consensual distribution of third-party sexual images, whose prevalence among youths has been shown to lie between 8.4 and 15.6% [2].…”
Section: Introductionmentioning
confidence: 99%